Electromagnetic Compatibility in Spacecraft Launches. Analysis and Interpretation of the Phenomenon Using Statistical Correlations (2025)
This thesis presents an exploratory analysis of the electromagnetic environment faced by spacecrafts during commercial launches to Low Earth Orbit (LEO), considering both radiated emission levels and electromagnetic compatibility (EMC) requirements as described in various launch providers’ Payload User’s Guides (PUGs). Correlation analyses and cluster-based segmentation were applied to identify which structural and operational variables influence emissions and constraints. Globally, the type of propulsion system (ρ = –0.81) and rocket L/D dimensions ratio (ρ = –0.46) were found to correlate with launch vehicle emissions, while payload constraints were mainly influenced by the mission type (ρ = –0.55) and payload capacity (ρ = –0.33). In specific clusters, other variables such as vehicle mass (ρ = 0.81), number of stages (ρ = –0.81), and fairing L/D ratio (ρ = 0.94) also showed associations with frequency range or electric field intensity. Regarding launch sites, it was found that LC-36 tends to generate higher emissions relative the launch vehicle itself and in some cases, these emissions also exceed the maximum allowed for the spacecrafts. Although no quantitative relationship was found between environmental conditions and launch frequency, most launch sites are located in Köppen CFA and CSB climates, due more to logistical and infrastructure factors than environmental suitability. In terms of EMC requirements, 52 entries were identified across 11 categories. Most are general guidelines or non-binding recommendations, with limited normative references and test criteria, highlighting the urgent need for clearer standardization—particularly for the validation of fully integrated systems.